HUBUNGAN PERAN KELUARGA SEBAGAI PMO (PENGAWAS MENELANOBAT) DENGAN KEJADIAN DROP OUT PADA PASIEN TBPARU DI POLI PARU RSUD SIDOARJO - Santoso, Windu; Maya Sari, Linda (JURNAL KEPERAWATAN SEHAT, 2015)
Tuberculosis is known as TB which it is contaminant disease caused by basil mycobacterium tuberculosis. The calculation of TB patient is increase from year because the spreading of TB is fast and easily. Unfortunately TB patient always disobey in using medicine. Therefore, they get drop out, the condition will fail for curing. In fact, the disease will spread more dangerous to others. PMO is a person who control and motivate the patient from drop out. In this case a family have a role for this curing. Because the psychological factor between the patient make the curing more easily. The research was analytic research with cross sectional. The role of family as PMO was independent variable and drop out was dependent variable. The research used consecutive sampling. The population in this research was using the family from TB patient as a new case in RSUD Sidoarjo. The sample in the research was 38 people. The analysis used spearman rho. The conclution from the research was a relationship between the role of family as PMO with drop out of TB. The variable refered p = 0,0000 (p < α 0,05). PMO should support the patient in using medicine, so it will prevent the patient from drop out.Keywords : Tuberculosis, Role, Drop Out